CHOQUEQUIRAO AND TEXTILE FOR THE GODS AND ELITE INCA - Apaza Huamani, John (2014)
The Incan society, as well as other complex and ideological societies, within its organization, confirms different activities to satisfy its basic and also ideological necessities; one of these activities is based in textile making with useful, political and religious or other goals, which are conceived in Incan social behavioral patterns and these would characterize the designation of textiles for a specific social level. The Archaeological and Monumental site of Choquequirao, because of the complexity of its architectural and urban characteristics, should be understood from the conception of the planning of Cusco. It is true that the construction of its buildings was developed on and in relation of the difficult topography. This will maintain the conceptual organization patterns of the planning of Cusco; that would be the concept idea to build «New Cuzcos» which were mentioned by Cieza de León and Bernabé Cobo in chapters LXXVII and XVIII respectively and analyzed by Hyslop in Inkawasi and Morris in Huanucopampa.